2021
DOI: 10.3390/cells10040854
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conjugation of NEDD8 to the N-Terminus of a Model Protein Can Induce Degradation

Abstract: While the role of ubiquitin in protein degradation is well established, the role of other ubiquitin-like proteins (UBLs) in protein degradation is less clear. Neural precursor cell expressed developmentally down-regulated protein 8 (NEDD8) is the UBL with the highest level of amino acids identified when compared to ubiquitin. Here we tested if the N-terminal addition of NEDD8 to a protein of interest could lead to degradation. Mutation of critical glycine residues required for normal NEDD8 processing resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“…In other instances, such as N-terminal fusion of SUMO, there is little to no impact either protein stability or antigen presentation (22). We have recently reported the N-terminal fusion of NEDD8 to a protein induces rapid degradation (25) and in this report sought to determine if the induction of protein degradation by NEDD8 fusion would enhance antigen presentation. By comparing cells infected with rVV expressing the different constructs, we were able to directly compare the effect of NEDD8-fusion with ubiquitin fusion and found that while NEDDylation of the cytosolic form of ovalbumin increased the rate of antigen presentation, it was not as efficient as ubiquitin fusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In other instances, such as N-terminal fusion of SUMO, there is little to no impact either protein stability or antigen presentation (22). We have recently reported the N-terminal fusion of NEDD8 to a protein induces rapid degradation (25) and in this report sought to determine if the induction of protein degradation by NEDD8 fusion would enhance antigen presentation. By comparing cells infected with rVV expressing the different constructs, we were able to directly compare the effect of NEDD8-fusion with ubiquitin fusion and found that while NEDDylation of the cytosolic form of ovalbumin increased the rate of antigen presentation, it was not as efficient as ubiquitin fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture, Transfection, and siRNA depletion L/K b , EL4, EL4/NC NEDD8-ova, EL4/ova and EL4/SCRAP-GFP cell lines have been previously described (5,25,27). All EL4-derived cells were grown in RPMI 1640 supplemented with 10 mM HEPES, Glutamax, and 7.5% fetal calf serum (all from Thermo Fisher) and were incubated at 37°C and 6% CO2.…”
Section: Plasmids Antibodies and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…N-terminal fusion proteins were created where the C-terminal glycine residues of NEDD8 were mutated to alanine which prevented removal of NEDD8 from the target protein, such as GFP or chicken ovalbumin. This modification resulted in an increased rate of degradation of the fusion protein demonstrating that N-terminal modification by NEDD8 can lead to a proteins degradation similar to N-terminal fusion of ubiquitin [78]. Interestingly, degradation of these substrates was blocked by both proteasome inhibition and by inhibition of autophagy, suggesting that there are multiple ways for cells to degrade NEDDylated proteins.…”
Section: Protein Degradationmentioning
confidence: 98%